2017
DOI: 10.3389/fphys.2017.00802
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Stomach Smooth Muscle Force Depends on History-Effects

Abstract: The stomach serves as food reservoir, mixing organ and absorption area for certain substances, while continually varying its position and size. Large dimensional changes during ingestion and gastric emptying of the stomach are associated with large changes in smooth muscle length. These length changes might induce history-effects, namely force depression (FD) following active muscle shortening and force enhancement (FE) following active muscle stretch. Both effects have impact on the force generating capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 89 publications
(145 reference statements)
7
27
0
Order By: Relevance
“…Finally, also a more realistic mechanical model of the gastric tissue should be employed. It is well‐known that the gastric tissue exhibits inhomogeneous and in general also anisotropic mechanical properties, which may also strongly depend on the age of an individual . Exploring the precise effect of the mechanical properties on the electro‐mechanical coupling might be a key to better understand the origin of certain gastric pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, also a more realistic mechanical model of the gastric tissue should be employed. It is well‐known that the gastric tissue exhibits inhomogeneous and in general also anisotropic mechanical properties, which may also strongly depend on the age of an individual . Exploring the precise effect of the mechanical properties on the electro‐mechanical coupling might be a key to better understand the origin of certain gastric pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a few papers on the constitutive behavior of the esophagus, [53][54][55][56][57] small intestine, [58][59][60][61][62][63][64] and large intestine, [58,61,[65][66][67][68][69][70][71] and around 20 on the mechanical properties of the gastric wall. [61,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] These revealed that the constitutive properties and thickness of the different layers of the gastric wall differ significantly between different regions of the stomach, corresponding to their respective physiological functions. Most papers on gastric tissue mechanics report results of uniaxial tests only, [61,[72][73][74][75][76]79,…”
Section: Gastric Wall: Solid Mechanicsmentioning
confidence: 99%
“…There have been a few papers on the constitutive behavior of the esophagus, small intestine, and large intestine, and around 20 on the mechanical properties of the gastric wall. These revealed that the constitutive properties and thickness of the different layers of the gastric wall differ significantly between different regions of the stomach, corresponding to their respective physiological functions. Most papers on gastric tissue mechanics report results of uniaxial tests only, which are insufficient to characterize the biaxial deformation (in both circumferential and longitudinal direction) observed in vivo, noting the in general significant anisotropy of gastric tissue.…”
Section: Anatomy and Physiology Of The Human Stomachmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, contraction tests on mesenteric arteries of rats, human tracheal tissues and smooth muscles of porcine stomach show a relatively similar ratio between the active and passive stress at optimal muscle length. [8,57,61] Therefore, it is assumed that the ratio between the active stress at optimal muscle length and the corresponding passive stress is the same for both pig common carotid artery and human abdominal aorta. Hence, the experimental length-tension behavior is scaled in the vertical direction (along the stress axis) accordingly, see Figure A1(b).…”
Section: Appendix A: Experimental Data Scalingmentioning
confidence: 99%